Roles of Al2O3 coating layer on an ordered mesoporous Ni/m-Al2O3 for combined steam and CO2 reforming with CH4 - Yu, Ji Su; Park, Jae Min; Kwon, Jae Hyeon; Park, Kyung Soo; Choung, Jin Woo; Park, Myung June; Bae, Jong Wook (Fuel, 2023)
To enhance catalytic and thermal stability of Ni nanoparticles for a combined steam and CO2 reforming with CH4 (CSCR), the utilization of an ordered mesoporous Al2O3 support with ∼6 nm of average pore diameter (Ni/m-Al) was proposed in terms of spatial confinement effects of the Ni nanoparticles with the help of successive Al2O3 overlayer protective layers (Ni/m-Al@Al). At an optimal amount of Al2O3 coating layers less than ∼3 wt%, the much higher catalytic activity and stability were observed on the Ni/m-Al@Al(3). The synergy effects of Al2O3 overlayers on the ordered mesoporous Ni/m-Al were mainly attributed to the formation of strongly interacted Ni-Al2O3 interfaces as supported by its higher XPS binding energy in the spatially restricted mesoporous m-Al channels with the protective metal oxide overlayers. Those structures were also responsible for the suppressed migrations of the spatially confined Ni nanoparticles to the outer m-Al surfaces by Al2O3 protective overlayers, which resulted in an excellent long-term stability with small coke depositions by preserving the original Ni nanoparticle sizes.
Keywords: CH 4; Coke formation; Combined steam and CO2 reforming with CH4 (CSCR); Ni Nanoparticles; Ordered mesoporous; Ordered mesoporous al2O3 (m-al); Overlayer al2O3 coating; Overlayers; Resistance to coke formation; Thermal stability of ni nanoparticle; Combined steam and CO2 reforming with CH4 (CSCR); Ordered mesoporous Al2O3 (m-Al); Overlayer Al2O3 coating; Resistance to coke formation; Thermal stability of Ni nanoparticles